Development of Sexual Education Animation Videos to Improve Sexual Understanding and Understanding of Forms of Sexual Harassment Behavior of Yogyakarta Elementary School Students - Yunita, Rosalia Nana; Wangid, Muhammad Nur (Ridwan Institute, 2024)
Sexual education has a crucial role in providing understanding to children about reproductive organs, prevention of sexual violence, and maintenance of intimate organs. This study aims to develop learning media in the form of sexual education animation videos to improve sexual understanding and understanding of forms of sexual harassment behavior in elementary schools. ADDIE research and development methods (Analysis, Design, Development, Implementation, and Evaluation) are used in this product development process. Needs analysis was conducted through interviews with guidance and counseling teachers, as well as classroom teachers in several elementary schools in Yogyakarta. The development phase involves material design, animation video creation, validation by media experts and material experts, as well as field trials. Evaluation is carried out to correct product deficiencies before they are widely implemented. The development results include animated sexual education videos that received